Integrating Tyler and Banks' Theories in Curriculum Development: A Tracer Study Approach at UIN Sunan Kalijaga - Darnela, Lindra; Sugitanata, Arif; Mughits, Abdul (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
Higher education in Indonesia plays a pivotal role in preparing a generation ready for the professional world. The curriculum of the Master's Program in Sharia Science at UIN Sunan Kalijaga Yogyakarta is integral to this mission. However, this research identifies gaps in the curriculum that do not fully align with alumni needs and job market demands. A field study involving 104 alumni from September 2018 to August 2022 was conducted using a descriptive-analytical method with an empirical approach. Data was collected via a survey sent to alumni and analyzed using Ralph W. Tyler's theory and James A. Banks' multicultural education theory. Findings reveal that courses like Fiqh Studies, Sharia Science, and Islamic Family Law in Indonesia were highly valued and should be further developed. Conversely, courses such as Falak Science and Arabic Text Reading were seen as less relevant and suggested for removal. Additionally, the replacement of the final project with journal publication was criticized. The analysis suggests that the curriculum should evolve to better reflect societal diversity and complexity. The proposed changes emphasize developing relevant courses and revising or eliminating those deemed less beneficial. These recommendations aim to ensure that the Sharia Science Master's Program remains responsive, inclusive, and capable of producing graduates who can compete in the global era.